2009
DOI: 10.3113/fai.2009.1094
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Three-Dimensional Analysis of Hindfoot Kinematics

Abstract: The data elucidates the baseline segmental motion for comparison with symptomatic subjects which could help us to better understand pathokinematics of various foot and ankle pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…Imai et al [22] reported on the translation of each joint in the hindfoot with ankle from neutral to maximum dorsiflexion or platarflexion using the centroid point of each bone. However, the joint translation is not purely indicated in the study, as the translation was partially influenced by bone rotation and the hindfoot has a complex structure.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Imai et al [22] reported on the translation of each joint in the hindfoot with ankle from neutral to maximum dorsiflexion or platarflexion using the centroid point of each bone. However, the joint translation is not purely indicated in the study, as the translation was partially influenced by bone rotation and the hindfoot has a complex structure.…”
Section: Discussionmentioning
confidence: 99%
“…3). Foot and ankle positions were set to be neutral in all axes to make a vertical line connecting the center of the heel and the second metatarsal, with the tibial shaft through the ankle center horizontal and parallel to the CT table [14,22]. CT scanning using a 256 multi-slice CT scanner (100 kV × 80 mA, volume EC, 512 × 512 matrix; 2.5 mm thickness; 2 mm interval; the Philips Brilliance 256, Philips Medical Systems, the Netherlands) was carried out from the axial plane 10 cm proximal to the ankle joint.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Wen et al (2012) reported that the rotational and translational change of the talocalcaneal joint had little influence on the change of the MLA. In addition, several studies (Imai et al, 2009;Imai et al, 2011;Kido et al, 2011;Ledoux et al, 2006) and our previous study (Zhang et al, 2013) had investigated the rotational and translational change of these three joints under loading in both healthy foot and stage II PTTD flatfoot, using three-dimensional reconstructed loading CT image data. However, to the best of our knowledge, no previous study had reported the correlation between the kinematics of the talocalcaneal joint, the talonavicular joint and the calcanocuboid joint and the change of the …”
Section: Introductionmentioning
confidence: 99%